Profiles of family routines during adolescence associated with profiles of health behaviors in young adulthood. (April 2020) - Abar, Caitlin C; Koban, Kaitlyn; Farnett, Sarah; Mendola, Kayla; Clark, Gabrielle
This study examined associations between profiles of family routines in early adolescence and profiles of health behaviors during young adulthood. In a sample of 4565 individuals, latent transition analysis indicated individuals in a family characterized by low involvement in adolescence were most likely, across classes, to demonstrate a profile characterized by substance use in young adulthood. The high-involvement class during adolescence was least likely to be a substance user but was relatively likely to be in the poor diet and exercise class during young adulthood. Results highlight the utility of examining complex family influences on health using person-centered methods.